(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The species composition of soil algae and micromycetes was studied in forest plantations and cretaceous chalk outcrops in the Eastern Steppe of Ukraine within the Kharkiv region. The systematic structure of mycobiota and algaeflora of the studied plots was similar to the species contents in forest cenoses of Eastern Europe, with the prevalence of Penicillium fungi and Chlorophyta and Cyanophyta algae. The total species diversity of micobiota was equally rich in forest plantations and on chalk outcrops, whereas algae species diversity was higher in the forest soils. In forest plantations and on chalk outcrops with woody coverage the changes of the algae species number with the soil depths, as well as during comparison of different plots, were directed oppositely to that of changes of micromycetes species number. It was shown that the similarity in species composition of micromycetes and algae in all types of soils under woody covering depends mostly on the territorial distance between studied plots, and under grassy covering – mostly on the phytocenosis contents.